RETRACTED: Interpersonal relations in the teaching staff and pro-environmental behavior of teachers of general educational organizations - Boiko Olga; Mitichkina Olga; Petrenko Elena; Chubova Irina (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001